Z Benedyktem XVI w drodze ku pełnej jedności chrześcijan - Warzeszak, Józef (Warszawskie Studia Teologiczne, 2017)
This present study aims to familiarise the Reader with some of the ideas contained in speeches of Benedict XVI – given at ecumenical meetings, chiefly with Protestants, but also during the general audiences on the Weeks of Prayer for Christian Unity and during the vespers for the conclusion of those Weeks. In his speeches, Benedict XVI indicates the positives that he sees in Martin Luther's teachings, emphasises the significance of the Declaration on the Doctrine of Justification, whilst also pointing out what still needs to be refined together. He states that one must not disregard theological issues in the ecumenical dialogue. The warnings of Benedict XVI against making mistakes in the ecumenical dialogue and in the interpretation of unity itself are significant. In each of his speeches, he encourages to deepen one's spiritual ecumenism, invites to pray for unity, demonstrates that complete and visible unity is, above all, the work of God. His encouragements to bear witness to God's priority in the Christian life together to the world, to oppose secularisation together, to defend the human dignity and life and their associated ethical values together are also important.